2020
DOI: 10.3390/su12239827
|View full text |Cite
|
Sign up to set email alerts
|

Rational Herding in Reward-Based Crowdfunding: An MTurk Experiment

Abstract: Crowdfunding is gaining popularity as a way of financing social sustainable initiatives. We performed a controlled economic experiment in MTurk by simulating a crowdfunding platform and developed a theoretical model that rationalizes herding behavior. The experiment was designed to test and quantify the causal effects of revealing specific information to prospective backers: (i) the number of early contributors already financing the project and (ii) positive opinions of other backers versus those of experts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
9
0
4
Order By: Relevance
“…One of the key methodological advancements of the current study is to provide configurational patterns of successful equity crowdfunding campaigns with either corporate or individual anchor investors. Previous research has identified the power of peer endorsement in attracting investment in crowd-based environments (Comeig et al, 2020). Hence, it could be argued that individual anchor investors would be deemed as more credible than corporate investors because prospective investors see themselves as more similar to individuals than corporations.…”
Section: Anchor Investors and Equity Crowdfundingmentioning
confidence: 99%
“…One of the key methodological advancements of the current study is to provide configurational patterns of successful equity crowdfunding campaigns with either corporate or individual anchor investors. Previous research has identified the power of peer endorsement in attracting investment in crowd-based environments (Comeig et al, 2020). Hence, it could be argued that individual anchor investors would be deemed as more credible than corporate investors because prospective investors see themselves as more similar to individuals than corporations.…”
Section: Anchor Investors and Equity Crowdfundingmentioning
confidence: 99%
“…En crowdfunding, el comportamiento gregario hace referencia al hecho de que las contribuciones iniciales estimulan las contribuciones subsiguien-tes. Por ello, cuando este comportamiento se utiliza para apoyar campañas con mayor probabilidad de conseguir el objetivo de financiación impuesto, esto es, su éxito y para no apoyar aquellas campañas que parecen tener más difícil su éxito, se considera un comportamiento gregario racional y ha sido ampliamente observado empíricamente (Zhang y Liu, 2012;Kuppuswamy y Bayus, 2017;Zaggl y Block, 2019;Chan et al, 2020;Comeig et al, 2020). La explicación teórica de este comportamiento de rebaño racional es que el comportamiento observado revela información que de otro modo no estaría disponible para el que toma la decisión, por lo que reduce la incertidumbre.…”
Section: Comportamiento Gregariounclassified
“…Entre estos sesgos destaca el comportamiento gregario o de rebaño, esto es, la tendencia a imitar las decisiones de financiación de los anteriores mecenas (Huang, Chen, 2006;Drehmann et al, 2007;Muchnik et al, 2013;Van de Rijt et al, 2014;Sasaki, 2019;Wessel et al, 2019). El efecto gregario se ha demostrado robusto en investigaciones anteriores como un acto racional que apoya campañas con mayor probabilidad de conseguir el objetivo de financiación impuesto, esto es, su éxito (Zhang, Liu, 2012;Kuppuswamy y Bayus, 2017;Zaggl y Block, 2019;Chan et al, 2020;Comeig et al, 2020).…”
Section: Introductionunclassified
“…Four different categories of crowdfunding can be identified: lending-based, donationbased, reward-based, and equity-based [80][81][82][83][84]. While lending-based crowdfunding aims at the crowd providing monetary funds in exchange for interest (much like a bank), donationbased crowdfunding works like one-to-one offline donations.…”
Section: Crowdfundingmentioning
confidence: 99%